2017
DOI: 10.1016/j.ihj.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogoniometry in psoriatic patients and its comparison with a control group

Abstract: Abnormalities in resting ECG and CGM and their correlation with disease severity raises concerns about the need for cardiovascular follow-ups of psoriatic patients, especially those with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Cardiogoniometry (CGM) is a spatiotemporal electrocardiologic method that can be used as a cardiovascular diagnostic tool. Poorzand et al conducted a study with 30 psoriatic patients and 30 age and sex-matched healthy individuals, without any history of CVD or traditional cardiovascular risk factors [ 33 ]. Electrocardiogram (EKG) and CGM were performed in these subjects.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiogoniometry (CGM) is a spatiotemporal electrocardiologic method that can be used as a cardiovascular diagnostic tool. Poorzand et al conducted a study with 30 psoriatic patients and 30 age and sex-matched healthy individuals, without any history of CVD or traditional cardiovascular risk factors [ 33 ]. Electrocardiogram (EKG) and CGM were performed in these subjects.…”
Section: Reviewmentioning
confidence: 99%
“…Electrocardiogram (EKG) and CGM were performed in these subjects. They noticed a remarkable difference between the psoriatic patients and the controls regarding myocardial ischemia score (-1.53 ± 2.63 vs. -0.46 ± 0.73, p = 0.037) [ 33 ]. There was a moderate correlation found between QT dispersion and the duration of the disease (r = 0.369, p = 0.022).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Seeck, et al 15) had reported the diagnostic value of CGM based on two different methods in the same population, so only the better results for CGM were selected. Excluded studies: Nineteen studies were excluded after reviewing the original text for the following reasons: The population of the study was other than candidates for elective angiography (n = 6), including Poorzand, et al 27) in patients with psoriasis, Spiliopoulos, et al 28) in patients who received a heart transplant, Tölg, et al 29) and Khamis, et al 30) in patients with acute coronary syndrome, Herrmann, et al 31) in patients after revascularization, and Sadeghpour, et al 32) in patients with left bundle branch block (LBBB); lack of reporting required diagnostic value parameters that could be used to construct or calculate true positive (TP), false positive (FP), true negative (TN), and false negative (FN) results (n = 4); [33][34][35][36] different types of articles including case reports, narrative reviews or congress abstracts with insufficient diagnostic parameters (n = 6); [37][38][39][40][41][42] the reference standard for CAD diagnosis was other than CAD stenosis in angiography (n = 3), including Weber, et al who used 43) stress/rest myocardial perfusion scintigraphy and Birkemeyer, et al who used 44) MRI. Furthermore, the study of Brown, et al was also excluded due to the lack of reported sample size of patients with significant coronary stenosis; 45) however, the primary aim of this study was to assess the ability of CGM to detect physiologically significant coronary stenosis defined by fractional flow reserve (FFR).…”
Section: Study Selectionmentioning
confidence: 99%